Earthy and Musty Off‐Flavor Episodes in Catfish Split‐Pond Aquaculture Systems. (12th February 2018) - Schrader, Kevin K.; Tucker, Craig S.; Brown, Travis W.; Whitis, Gregory N.
Abstract: The interest and use of variations of partitioned aquaculture systems (PAS) by the catfish farming industry in the southeastern USA continues to grow. Split‐pond systems, one type of PAS, are designed to improve the management of dissolved oxygen levels and fish waste products (e.g., ammonia) compared with conventional earthen ponds that have been used for many decades. While recent studies of split‐pond systems have focused on design, water flow rates, and management practices, there has not been any assessment of the occurrences and intensities of common "off‐flavor" episodes in these split‐ponds. For the current study, pond water samples were collected from split‐ponds at a commercial fish farm in western Alabama and at a research facility in western Mississippi approximately every 3–4 weeks during the fish grow‐out period (May to November) during 2014 and 2015. In addition, fillet samples from hybrid catfish (Channel Catfish Ictalurus punctatus × Blue Catfish Ictalurus furcatus ) were obtained in late summer and autumn from these same split‐ponds. Concentrations of the "earthy" and "musty" off‐flavor compounds geosmin and 2‐methylisoborneol (MIB), respectively, in water and fillet samples were determined. Sensory analysis was also performed on catfish fillets collected during 2014. The highest geosmin and MIB concentrations detected in split‐pond water during the study were 898 and 22, 651 ng/L, respectively. Geosmin and MIB concentrations in split‐pond water were often higher in summer and autumn, and concentrations were similar to those reported previously for conventional ponds. The highest geosmin and MIB concentrations detected in fillets during the study were 1, 712 and 29, 851 ng/kg, respectively. Concentrations of these compounds in fillets and the description and intensities determined via sensory analysis were similar to those reported previously for off‐flavor catfish from conventional ponds. Accordingly, catfish farmers using split‐ponds can use similar management approaches as those used to mitigate earthy and musty off‐flavor problems in catfish raised in conventional ponds (e.g., applications of algicides).